Mind the gap a study on the barriers to sports participation faced by persons with psychosocial disabilities - Gaite, Anne Dominique C. 2002-
An area for fostering community engagement is sports, yet Persons with Disabilities (PWDs), specifically those with Psychosocial Disabilities are frequently left out of these communities in their formative years. The study aims to determine the barriers to sports participation faced by Persons with Psychosocial Disabilities through qualitative research and individual interviews. Specifically, this study looks into identifying and classifying the different types of barriers in sports non-participation faced by the participants, and analyzing the types of barriers in relation to inclusive sports. The participants of this study were five Persons with Psychosocial Disabilities aged 19 to 24 years old and were obtained via convenience sampling. Their responses were analyzed using Thematic Analysis to identify common themes and barriers. The study established that the following barriers- biological and physical, psychological, economic, environmental and structural, social and organizational, and personal and interest, play a role in preventing sports participation to varying extents. While for some participants it varied in prominence, their psychosocial disorder contributed to most of their psychological barriers and led to some of their biological and/or social barriers as well. For inclusive sports for persons with Psychosocial Disabilities, one must consider Bio-psycho-social (BPS) model when assessing their well-being in connection to their disorders, their material conditions which may prevent their participation, and their individual differences.